2013
DOI: 10.1902/jop.2012.120484
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Clinical and Radiographic Periodontitis Measurements During Periodontal Maintenance

Abstract: Background To examine the association between clinical and radiographic periodontitis measurements during two years of periodontal maintenance. Methods Secondary analyses were performed from a two-year, double-blind, placebo-controlled, randomized clinical trial evaluating the efficacy and safety of subantimicrobial dose doxycycline (SDD) in 128 postmenopausal osteopenic women with moderate to severe chronic periodontitis. Relative clinical attachment level (RCAL) and probing depth (PD) measures were made. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…This is important, given the strong association of greater ABL with periodontitis observed in the study ( P <0.001; data not shown), suggesting that ABL, a hallmark and distinctive feature of periodontitis, is a reflection of a patient's periodontitis status. Indeed, the authors have previously shown that relative clinical attachment level (relative to the occlusal surface) and ABL were significantly and positively associated at baseline ( P <0.0001) in a study examining postmenopausal women with periodontitis and systemic osteopenia 30 . In the current study, for sites in patients with RA with high ABL (>8.80%), the average clinical AL (relative to the CEJ) was 3.75 mm.…”
Section: Discussionsupporting
confidence: 51%
“…This is important, given the strong association of greater ABL with periodontitis observed in the study ( P <0.001; data not shown), suggesting that ABL, a hallmark and distinctive feature of periodontitis, is a reflection of a patient's periodontitis status. Indeed, the authors have previously shown that relative clinical attachment level (relative to the occlusal surface) and ABL were significantly and positively associated at baseline ( P <0.0001) in a study examining postmenopausal women with periodontitis and systemic osteopenia 30 . In the current study, for sites in patients with RA with high ABL (>8.80%), the average clinical AL (relative to the CEJ) was 3.75 mm.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, alterations in CAL were negatively correlated with PPD at baseline in subjects with high oxidative status. Recent research has suggested that baseline PPD is associated with subsequent alveolar bone density and height loss in postmenopausal osteopenic females undergoing periodontal maintenance [ 39 ]. However, it have been indicated that sites with deep PPD showed more attachment level gain after 3 months of scaling and root planning than those with shallow PPD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously hypothesized that ABD loss may precede ABH loss. However, we have since examined the data from this group of women and failed to detect this hypothesized sequence in periodontitis progression, possibly because the postmenopausal women in this study exhibited minimal local or systemic bone loss over the 2‐year study . The current study's finding that ABD loss was more common than periodontitis progression (measured by either ABH or RCAL) suggests that change in ABD may be a more sensitive diagnostic measure in patients undergoing periodontal maintenance.…”
Section: Discussionmentioning
confidence: 63%
“…Baseline, 1‐year, and 2‐year serum samples were assayed in 2008 by one investigator (Dr. Hsi‐Ming Lee). Details on the consenting process, which was approved by the Institutional Review Boards of the University of Nebraska Medical Center and Stony Brook University, are published as are other aspects of the original trial and its supplement …”
Section: Methodsmentioning
confidence: 99%